IMPACT OF CORPORATE SOCIAL RESPONSIBILITY DIMENSIONS ON MINING FIRM VALUE IN INDONESIA - Inggrid Claudia Islam; Intan Aprilianiswah B; La Ode Almana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) dimensions on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2019 period. The sample was determined using a purposive sampling method based on specific criteria, resulting in six sample companies selected from a total of 47 listed mining firms. The study employed secondary data obtained from companies’ annual and sustainability reports. Data analysis was conducted using descriptive statistical analysis and multiple linear regression, processed with SPSS version 25. The results indicate that simultaneously, the economic, environmental, and social dimensions of CSR have no significant effect on firm value. Partially, the economic and environmental dimensions show a positive but insignificant influence on firm value. In contrast, the social dimension of CSR has a negative and significant effect on firm value. These findings suggest that CSR implementation, particularly in the social dimension, has not yet been fully perceived by the market as a value-enhancing factor for mining companies.